A Feminist Moral-Political Economy of Uneven Reform in Austerity Britain: Fostering Financial and Parental Literacy. Issue 6 (1st November 2016) - Montgomerie, Johnna; Tepe-Belfrage, Daniela
Abstract: This article draws on two empirical case studies to draw out the way in which the causes of poverty in austere times in the UK are inverted, from their socio-economic causes to making the poor themselves responsible for their misery but also responsibilising them for fighting their way out of poverty. We particularly focus on how austerity policy in the UK has involved a return of moral language of the 'undeserving poor'. We highlight the way in which this 'moral-political economy' has gendered effects, targeting single-mothers and their children and families, through the lens of 'literacy'. The first case study show how promoting 'financial literacy' is seen to solve indebtedness of the poor and the second case study highlights how 'parental literacy' is employed to turn around 'troubled families'. Indeed, these two studies demonstrate how the morality of austerity is shaped through deeply gendered practices of the everyday in which women's morality is what ultimately needs reforming.